PRELIMINARY REPORT ON STRUCTURES OF FOREFINGER POINT, ENDERBY LAND, EAST ANTARCTICA - イシカワ, マサヒロ; モトヨシ, ヨウイチ /; ISHIKAWA, Masahiro; MOTOYOSHI, Yoichi; FRASER, Geoffrey L. (National Institute of Polar Research, 1994)
P(論文) Granulite-facies metamorphic rocks of Forefinger Point, which lie on the Casey Bay coastline in Enderby Land, have been affected by three stages of folding, shear zone formation, and intrusion of pegmatite. The peak metamorphic structural evolution was characterized by the development of F_n isoclinal to close buckling folds. This deformation was associated with the coexistence of orthopyroxene+sillimanite±quartz, and was followed by the formation of cordierite and symplectites of cordierite+sapphirine, orthopyroxene+cordierite+sapphirine in response to subsequent isothermal decompression. These symplectic intergrowths are generally unstrained except in some cordierite domains where cordierite exhibits a weak mineral lineation, implying that intense ductile deformation had ceased before the decompressional reactions : orthopyroxene+sillimanite+quartz=cordierite, orthopyroxene+sillimanite=cordierite+sapphirine, garnet+quartz=orthopyroxene+cordierite. Although the Forefinger Point granulites have undergone high strain deformation under peak metamorphic conditions, they experienced only low and local strain deformation after peak metamorphism. The post-peak-metamorphic structural evolution was characterized by the development of F_<n+1> open to gentle buckling folds, narrow shear zones and emplacement of pegmatite. departmental bulletin paper